Re-Envisioning Immigrant Integration: Toward Multidirectional Conceptual Flows. Issue 2 (3rd April 2023) - Abdelhady, Dalia; Norocel, Ov Cristian
Abstract: This special issue collects articles, which aim to re-envision integration, dislodging the previously monodirectional conceptual flow sourced in the Global North. Jointly, the articles pursue a critical scholarship contributing to multicentric knowledge production, disrupting binaries of integrated/nonintegrated, inclusion/exclusion, citizen/non-citizen, or indeed self/other. They evidence ambivalent subject positions, neither fully-included nor fully-excluded, and engender forms of belonging to the places immigrants are momentarily located in, albeit without a steadfast position granting them rights. The collected articles also emphasize the various scales of integration, be it wider global or regional flows, as well as more localized, zoomed-in, and ephemeral manners of integration.